Muntu: the Diaspora of African Philosophical Thought inChangó, el gran putas [Changó, the Biggest Badass] by Manuel Zapata Olivella (2016)
The problem of diasporic phenomena in America is a significant element in Changó, el gran putas . In this novel, the African exodus is related to Muntu philosophy. This philosophy brings together African knowledges composed of diverse elements that reemerge in America, where they are transformed in a context of postcolonial cultural exchange. In Changó , Muntu philosophy allows us to analyze the pos- sibility of creating an alliance between africans and mestizos committed to the freedom of America, at the same time as it becomes a metaphor for American mestizaje ; an opportunity to see the History of this continent from a literary point of view which engages different dimensions of the human being. This study is a reflection about the way in which the different philosopical categories of Muntu (Kintu, Kun - tu, Hantu and Muntu) are developed and ad[a/o]pted from a literary/philosophical perspective, inquiring into their relevance in the work.